Micro- and nanoflows : modeling and experiments /: modeling and experiments. ([2018]) - Rudyak, Valery Ya; Rudyak, Valery Ya; Aniskin, Vladimir M; Maslov, Anatoly A; Minakov, Andrey V; Mironov, Sergey G
No abstract available